2015
DOI: 10.1016/j.exger.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced differential gene expression and acetyl-CoA metabolism in a longevity model of the nematode Caenorhabditis elegans

Abstract: Previous studies have shown that exposing adults of the soil-dwelling nematode Caenorhabditis elegans to concentrations of ethanol in the range of 100 – 400 mM results in slowed locomotion, decreased fertility, and reduced longevity. On the contrary, lower concentrations of ethanol (0.86 – 68 mM) have been shown to cause a two- to three-fold increase in the life span of animals in the stress resistant L1 larval stage in the absence of a food source. However, little is known about how gene and protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Any kind of environmental stress will have a potential impact on the lifespan of the nematode (Patananan et al 2015). Moreover, lifespan analysis is the first and foremost indication in aging analysis (Tissenbaum 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any kind of environmental stress will have a potential impact on the lifespan of the nematode (Patananan et al 2015). Moreover, lifespan analysis is the first and foremost indication in aging analysis (Tissenbaum 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In C. elegans benzaldehyde is usually used as a positive control for chemotaxis (Rabinowitch et al 2014). In a recent study, it was proved that worms show no chemotaxis towards ethanol (Patananan et al 2015). Our group has previously reported that C. elegans avoid Vibrio alginolyticus (Durai et al 2011) whereas it gets attracted to Cronobacter sakazakii (Sivamaruthi et al 2011), which may be by the alteration of serotonin transporter (Sivamaruthi et al 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Caenorhabditis elegans has been proven to be an excellent experimental system to assess the physiological activity of antioxidants, due to its short three‐week lifespan, easy culture conditions and rapid generation time (Kenyon ; Patananan and others ). It has been demonstrated that 60% to 80% of human gene homologues exist in C. elegans (Kaletta and Hengartner ).…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that 60-80% of human gene homologues have been identified in C. elegans (Kaletta & Hengartner, 2006). C. elegans has been increasingly applied to investigate the effect of pharmacologically active compounds on antioxidation and ageing processes (Gruber, Ng, Poovathingal, & Halliwell, 2009;Patananan, Budenholzer, Eskin, Torres, & Clarke, 2015). A number of antioxidants including coenzyme Q10 (Fischer, Niklowitz, Menke, & Döring, 2014), resveratrol (Regitz, Fitzenberger, Mahn, Dußling, & Wenzel, 2016) and tea polyphenols (Deusing et al, 2015) have been found to extend the lifespan of C. elegans.…”
mentioning
confidence: 99%